Abnormal aggregation of myeloid-derived suppressor cells in a mouse model of cyclophosphamide-induced premature ovarian failure. (2nd November 2019) - Han, Mutian; Cheng, Hongbo; Wang, Jiaxiong; Yu, Yi; Wang, Fuxin; Zhu, Rui; Wang, Wei; Yang, Shenmin; Li, Hong
Abstract: Oocytes are extremely sensitive to radiation and chemotherapy, and premature ovarian failure (POF) is one of the side effects of anti-tumor therapy. The pathogenesis of POF is very complex and still not fully elucidated. A mouse POF model was established after 14 days of cyclophosphamide injection. POF mice presented ovarian atrophy, destroyed follicular structure, a reduction in the number of primordial and mature follicles, and an decrease in the number of corpora luteal along with increased level of follicle-stimulating hormone (FSH), decreased levels of estradiol (E2), and anti-Mullerian hormone (AMH). Additionally, the proportion of bone marrow myeloid-derived suppressor cells (MDSCs) in peripheral blood, spleen, and ovarian tissue increased. MDSCs were mainly distributed around follicles and corpora luteal. Levels of mTOR and p-mTOR increased in ovarian tissue and inhibition of mTOR with rapamycin reduced the aggregation of MDSCs in peripheral blood, spleen, and ovarian tissue. This investigation sheds new light on the modulatory role of mTOR and demonstrates that an increase in MDSC number may play a key role in the pathological reaction during POF. Inhibition of mTOR and reduction of MDSCs in the ovary may represent a novel strategy for the treatment of POF.